"UNLEASHING THE POWER: EMPOWERING WOMEN FOR A STRONGER ECONOMY" - Dr T. Sudha; Irshad Ahmad Reshi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Abstract: Despite significant progress in recent years, gender inequality remains a challenge in many countries, hindering the full potential of women and, consequently, the economy as a whole. This research paper explores the impact of women's empowerment on the economy and the measures that can be taken to increase women's participation in the workforce. Using a combination of qualitative and quantitative methods, the research analyses the current state of women's participation in the economy, the barriers they face, and the strategies that can be employed to overcome these barriers. The paper argues that empowering women can lead to increased economic growth, improved social well-being, and enhanced human development. The research provides insights into the potential benefits of empowering women for the economy and society as a whole and identifies the necessary steps that can be taken to achieve this goal.